Synthesis of Indole Derivatives via Aryl Triazole Ring-Opening and Subsequent Cyclization - Aleksejs Burcevs; Armands Sebris; Irina Novosjolova; Anatoly Mishnev; Māris Turks (Molecules)
A metal-free two-step synthetic approach for obtaining indole derivatives from aryl triazole fragment-containing compounds has been developed. In the first step, the Dimroth equilibrium, followed by nitrogen extrusion, Wolff rearrangement, and amine nucleophile addition, leads to the formation of N-aryl ethene-1,1-diamines. In the second step, the latter intermediates are cyclized into the target 1H-indoles in the presence of iodine. The developed method ensures the synthesis of indoles that possess N-substituents at the indole C2 position. Depending on the applied N-nucleophile, the indolization step provides a selectivity either towards 1H-indoles or 1-aryl-1H-indoles.